2018
DOI: 10.17586/1606-4313-2018-17-3-53-61
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fungal extract containing beta beta-glucans on the rheological characteristics of dough

Abstract: д-р техн. наук Л. ГАЧЕУ 2 , О. ОПРЯ 2 , канд. техн. наук М. М. ШАМЦЯН 1 1 Санкт-Петербургский государственный технологический институт (технический университет)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
2
Order By: Relevance
“…Future research will be conducted on the use of grape epicarp as an addition to bread making recipes. Theoretical and experimental analyzes will be performed regarding the chemical composition, the nutritional profile, the rheological behavior of the dough and the sensory analysis [13,14,15]. Different degrees of replacement of wheat flour with grape epicarp flour are considered, such as: 5%, 7.5%, 10%, 12.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Future research will be conducted on the use of grape epicarp as an addition to bread making recipes. Theoretical and experimental analyzes will be performed regarding the chemical composition, the nutritional profile, the rheological behavior of the dough and the sensory analysis [13,14,15]. Different degrees of replacement of wheat flour with grape epicarp flour are considered, such as: 5%, 7.5%, 10%, 12.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Известен дрожжевой хлеб из пшеничной муки, содержащий β-1,3/1,6-глюкан (из грибов вешенки обыкновенной) в количестве 2%, 1,4%, 1,0% и 0,6%. Анализ характеристик испеченного хлеба показал, что добавление к рецептуре теста грибного экстракта, содержащего бета-глюканы в концентрации 1 %, лишь менял цвет хлеба, делая его более коричневатым, увеличивал пористость мякиша и придавал ему несколько более кислый привкус, при этом вкус оставался приятным [12].…”
Section: рисунок 1 -продукты ежедневного рациона содержащие концентраты β-глюканаunclassified
“…Надо сказать, что в качестве источника β-глюкана многие авторы рассматривают частичную замену традиционного сырья овсяной мукой. Так, в рецептуре дрожжевого хлеба замена пшеничной муки в количестве 5-30% концентратом β-глюкана из зерна овса и ячменя замедлило процесс черствения опытного образца, однако с повышением содержания концентрата Дрожжевой хлеб из пшеничной муки, содержащий β-1,3/1,6-глюкан в количестве 2,0%, 1,4%, 1,0%, 0,6% [12] Майонез [10]…”
unclassified
“…The effect of a mushroom extract containing β-glucans on the rheological characteristics of wheat dough was studied by M. Frioui et al [13]. In the course of the study, it was found that mushroom extract is suitable as a functional component with insignificant changes of organoleptic properties.…”
Section: Introductionmentioning
confidence: 99%